Kinematical analysis of dismount of straight back somersault with a turn of 900°: a case study - Cheng, Q.; Zhou, J.; Gao, Z. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The techniques of dismount of straight back somersault with a turn of 900° performed by Tan Sixin (winner of all-round of China's gymnastics championships in 2011) and Jiang Yuyuan(winner of champion of the balance beam of World University Games in 2009) was filmed using 3-D camera method. The kinematics data were collected and analyzed by motion performance analysis system. The conclusions came out that overall execution of Tan Sixin was good, while the action of Jiang Yuyuan needed to be improved. The results of the analysis will provide a theoretical basis of balance beam training for athletics and trainer.